2021
DOI: 10.1016/j.annonc.2021.03.036
|View full text |Cite
|
Sign up to set email alerts
|

22P HER2-low vs HER2-zero metastatic breast carcinoma: A clinical and genomic descriptive analysis

Abstract: Conclusions: We would suggest the use of NGS rather than conventional RT-PCR to screen for the presence of a PIK3CA mutation in BC patients. Finally, given the not well-established applications of ctDNA analysis in the clinical management of BC, this meta-analysis could add intriguing insights supporting the introduction of liquid biopsy in clinical practice as a routine procedure.Legal entity responsible for the study: The authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The most commonly mutated genes in both ERBB2-low and ERBB2zero tumors were TP53 (34.3% and 48.2%, respectively) and PIK3CA (31.3% and 35.2%, respectively); FGFR1 amplification was more common in ERBB2-low (12.0%) than in ERBB2-zero (1.8%) tumors. 18 In addition, PDGFRA and MYC amplification were more common in ERBB2-low than ERBB2-zero (PDGFRA, 2.3% vs 0.28%; MYC, 8.1% vs 4.6%) tumors in another study of 991 patients with mBC. 7 Also, ERBB2-low tumors have been observed to have BRCA1/2 and other breast cancer predisposition genes less frequently than ERBB2zero tumors.…”
Section: Biological Characteristics and Role In Tumor Evolutionmentioning
confidence: 95%
See 3 more Smart Citations
“…The most commonly mutated genes in both ERBB2-low and ERBB2zero tumors were TP53 (34.3% and 48.2%, respectively) and PIK3CA (31.3% and 35.2%, respectively); FGFR1 amplification was more common in ERBB2-low (12.0%) than in ERBB2-zero (1.8%) tumors. 18 In addition, PDGFRA and MYC amplification were more common in ERBB2-low than ERBB2-zero (PDGFRA, 2.3% vs 0.28%; MYC, 8.1% vs 4.6%) tumors in another study of 991 patients with mBC. 7 Also, ERBB2-low tumors have been observed to have BRCA1/2 and other breast cancer predisposition genes less frequently than ERBB2zero tumors.…”
Section: Biological Characteristics and Role In Tumor Evolutionmentioning
confidence: 95%
“…It has been reported that ERBB2-low primary tumors are larger than ERBB2 IHC-0 tumors 20 and are more likely to be clinical node-positive. 13 In a retrospective analysis of 121 patients with metastatic breast cancer (mBC), 18 the most frequent phenotype of ERBB2low tumors was luminal B, and this phenotype was more prevalent among ERBB2-low (65.7%) than ERBB2-zero (37.0%) tumors. In a study of 285 patients with ERBB2-low early breast cancer, 13 82.8% were of the luminal subtype.…”
Section: Biological Characteristics and Role In Tumor Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in tumor size, tumor grading, Ki-67 proliferation rate, or nodal status between HER2-low and HER2 IHC 0 breast cancer exist 9 , 22 , 26 , 28 , 29 , 30 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ; however, they are not consistent across studies 9 , 23 , 26 , 27 , 37 , 41 , 45 , 46 , 47 and may depend on HR status. 9 , 22 , 40 , 48 Genomic alteration and prediction analysis of microarray 50 (PAM50) intrinsic subtype differences between HER2-low and HER2 IHC 0 tumors have been observed, 9 , 22 , 48 , 49 but these were largely dependent on HR status. 9 , 22 , 48 HER2-low tumors were more likely to have PIK3CA mutations and less likely to have TP53 mutations when HR subsets were combined; however, no differences in PIK3CA mutation prevalence were observed when HR subsets were analyzed separately, and differences in TP53 mutation prevalence were observed only among HR+ tumors.…”
Section: Clinicopathologic Features and The Prognostic Role Of Her2-l...mentioning
confidence: 99%